Effect of Moisture Content on the Yield of Mahogany Seed Oil - (:unkn) unknown (My University, 2023)
African Mahogany (Khaya senegalensis) is an important tree in Africa. A deciduous tree, reaching up to 35m in height on fertile soils. It has a diameter of up to 1.5 m with 8-16 m bole. The bark is dark grey or pink with red latex. The plant is commonly found in all the Northern States and around South Western States of Nigeria in the rain forest zone. The plant begins to produce fruit after 15 – 25 years throughout the dry season. The fruit is woody capsule, 4-10 cm long and dehisces at maturity. The seeds have a very low moisture content which is good for oil extraction hence its selection. For the purpose of this study, Mahogany seed, distillation apparatus, jaw crusher, water distiller, chiller, soxhlet extractor, oven, digital weighing balance, n-hexane, are the materials used for the extraction. According to Soxhlet procedure, oil and fat from solid material are extracted by repeated washing (percolation) with an organic solvent, usually hexane or petroleum ether. 325 g of mahogany seed was used in 25-x 80-mm thimble. The Sample has an oil yield of 63.58%, with a cake of 206.62g after extraction and a moisture content of 9% as a result of volatile substance due to high vapor pressures. Further studies on the extraction of oil from mahogany seed is recommended with method other than soxhlet extraction method using n-hexane as extracting solvent as the best method of extraction for end users.
Keywords: African Research